Stakeholder Participation for Legitimate Priority Setting: A Checklist - Maarten P.M. Jansen; Rob Baltussen; Kristine Bærøe (International Journal of Health Policy and Management, 2018)
Accountable decision-makers are required to legitimize their priority setting decisions in health to members of society. In this perspective we stress the point that fair, legitimate processes should reflect efforts of authorities to treat all stakeholders as moral equals in terms of providing all people with well-justified, reasonable reasons to endorse the decisions. We argue there is a special moral concern for being accountable to those who are potentially adversely affected by decisions. Health authorities need to operationalize this requirement into real world action. In this perspective, we operationalize five key steps in doing so, in terms of (i) proactively identifying potentially adversely affected stakeholders; (ii) comprehensively including them in the decision-making process; (iii) ensuring meaningful participation; (iv) communication of recommendations or decisions; and (v) the organization of evaluation and appeal mechanisms. Health authorities are advised to use a checklist in the form of 29 reflective questions, aligned with these five key steps, to assist them in the practical organization of legitimate priority setting in healthcare.